EFEKTIFITAS PUPUK DALAM BEBERAPA UKURAN SACHET TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) - Alia Rahma; Mardiana Wahyuni; Saroha Manurung (Agro Estate, 2019)
The productivity of oil palm plants is influenced by genetic factor planting materials, soil, climate, cultivation and plant maintenance. Nursery is the first step to prepare the prime plant material. In the implementation of the nursery, fertilization is one important maintenance factor and should be done with reference to 4T (Exactly Types, Dosage, Time and Method). Loss of fertilizer is an important thing to be controlled. This research is a conservation action by packing fertilizer in sachet bag and conservation treatment. The research was conducted in January 2019 – July 2019 at STIPAP. The study used a non factorial randomized block design with S one sowing system, S two, S three, and S four sachet systems of different sizes using conservation. The best treatment is the application of gauze sachet system (S four = 638 mesh) with conservation increasing the growth of seedling height (91,36 cm), stem diameter (50,80 mm), increasing chlorophyll (55,62 cci), increasing root wet weight 99,73 (44%) and canopy dry weight 55,10 (44%).